2021
DOI: 10.17582/journal.aavs/2022/10.2.270.276
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ensiling and Tannins Addition on Rumen Degradation Kinetics of Soy Sauce Residues

Abstract: | Condensed tannins (CT) and hydrolyzable tannins (HT) are secondary metabolites substances that are widely proposed as safe additives to improve protein utilization in ruminants. This study aimed to investigate the effect of tannins extracted from acacia and chestnut on the degradation kinetics of ensiled and non-ensiled soy sauce residue (SSR) in sacco. Two fistulated beef cattle (425±25 kg) fed a diet consisting of 80% Pennisetum purpureum and 20% concentrate was used to incubate the SSR samples (ensiled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The amount of gas produced in the rumen is representative and indicates the amount of feed that sheep can digest. A study by Sadarman et al [5] reported that ensiled agro-industrial by-products with no additives showed no significant difference. Contrary findings showed that adding up to 2% additive produced a significant difference.…”
Section: Effects Of Ensiled Coffee Skin On Gas Production Ruminal Flu...mentioning
confidence: 98%
See 2 more Smart Citations
“…The amount of gas produced in the rumen is representative and indicates the amount of feed that sheep can digest. A study by Sadarman et al [5] reported that ensiled agro-industrial by-products with no additives showed no significant difference. Contrary findings showed that adding up to 2% additive produced a significant difference.…”
Section: Effects Of Ensiled Coffee Skin On Gas Production Ruminal Flu...mentioning
confidence: 98%
“…In addition, the production of water spinach was unstable due to tropical conditions and limitations of the water. The ensiling technique is both favorable and technically possible due to its low cost and appropriateness for smallholder farmers in Indonesia [4,5]. The hematological and physiological profiles of sheep are influenced by various factors, including breed, age, environmental conditions, related heat stress, and transportation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation